2017
DOI: 10.1016/j.nmd.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry on a panel of Emery–Dreifuss muscular dystrophy samples reveals nuclear envelope proteins as inconsistent markers for pathology

Abstract: HighlightsAltered distribution of EDMD-linked proteins is not a general characteristic of EDMD.Tissue-specific proteins exhibit altered distributions in some EDMD patients.Variation in redistributed proteins in EDMD may underlie its clinical variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…In EDMD2 mature muscle, we observed mis-localization of Samp1 from the nuclear envelope of myonuclei. In fact, double immunolabeling of Samp1 and laminin alpha 2, which lines the basal lamina of myofibers, demonstrated that nuclei inside control muscle fibers were Samp1 positive and the protein was located at the nuclear periphery, which was previously reported in Reference [ 30 ], while interstitial nuclei presented a faint staining ( Figure 4 d). In EDMD2 myonuclei bearing the H506P LMNA mutation [ 32 ], Samp1 was mis-localized in the vast majority (80%) of examined myofibers ( Figure 4 d) possibly due to a loss of interaction with farnesylated prelamin A, which is dramatically reduced in EDMD2 muscle fibers [ 15 ].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In EDMD2 mature muscle, we observed mis-localization of Samp1 from the nuclear envelope of myonuclei. In fact, double immunolabeling of Samp1 and laminin alpha 2, which lines the basal lamina of myofibers, demonstrated that nuclei inside control muscle fibers were Samp1 positive and the protein was located at the nuclear periphery, which was previously reported in Reference [ 30 ], while interstitial nuclei presented a faint staining ( Figure 4 d). In EDMD2 myonuclei bearing the H506P LMNA mutation [ 32 ], Samp1 was mis-localized in the vast majority (80%) of examined myofibers ( Figure 4 d) possibly due to a loss of interaction with farnesylated prelamin A, which is dramatically reduced in EDMD2 muscle fibers [ 15 ].…”
Section: Resultssupporting
confidence: 78%
“…Although we observe a uniform distribution of Samp1 in the nuclear envelope, loss of prelamin A farnesylation [ 15 ] causes Samp1 mislocalization from the nuclear poles. Moreover, in EDMD2 myotubes, Samp1 is overall preserved at the nuclear envelope, which is reported in Reference [ 30 ], but it is missing from the nuclear poles. Thus, a protein platform including farnesylated prelamin A, SUN proteins, and Samp1 is located at the nuclear poles of myonuclei and it is disrupted in EDMD2.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Samp1 also interacts with the LINC complex protein, Sun1 22 , 23 , which is also implicated in EDMD. A recent study 32 showed that Samp1 distributed abnormally, in some, but not all EDMD patient cells. The strong and clear requirement for Samp1 in differentiation of C2C12 myoblasts presented here may provide new insights in the pathological development in EDMD.…”
Section: Discussionmentioning
confidence: 96%
“…21 Distinct, clinically useful immunohistochemistry findings have not been established in the other EDMD subtypes. 112…”
Section: Muscle Pathologymentioning
confidence: 99%